A note on cloning and analysis of the osteopontin gene with egg quality traits in two Chinese domestic ducks. Issue 6 (2nd November 2018) - Bai, D.; Lan, L.; Wan, Y.; Yan, M.; Lian, S.; Li, A.; Wu, X.
ABSTRACT: 1. Osteopontin ( OPN ) is a highly phosphorylated acidic glycoprotein that plays a crucial role in eggshell formation. In this study, an 893-bp cDNA sequence of the OPN gene, which encodes 180 amino acids, was obtained. 2. Polymorphisms of the OPN gene were analysed with DNA sequencing and polymerase chain reaction-single-strand conformation polymorphism methods in two Chinese domestic laying ducks (Jingding n = 100, Youxian n = 478, respectively). 3. One polymorphism was identified in exon 7 (NM_ 004676534.1:c.267T>C) of the OPN gene, with three genotypes: TT (both T allels weren't mutated (wild type)), TC (one T allel was mutated to C (heterozygote genotype)) and CC. (both T allels were mutated to C (homozygote 20 genotype)) Association analysis with egg quality traits in the two Chinese domestic laying ducks showed that the ducks with the CC genotype had significantly greater eggshell strength and eggshell thickness ( p < 0.05). Hence, the exon 7 267T>C polymorphism of the OPN gene is a potentially valuable genetic marker for laying duck breeding programmes.